Diagnosis and management of an unusual presentation of schwannoma in nasopharynx: a case report - Srilatha Kavarthapu; Kaushik Saha; Vasudha Singh; Venkata Krishna Sundeep Nalamolu; Manish Singh (Journal of Medical Case Reports)
Abstract Background Schwann cells are responsible for producing the myelin sheath that surrounds the axons in the peripheral nervous system. Benign tumors that originate from Schwann cells are called schwannomas or neurilemmomas. These tumors typically present as slow-growing, solitary, encapsulated masses, often associated with nerve trunks. Schwannomas are relatively rare, with 25–45% of cases occurring in the head and neck region. Case presentation This report aims to describe the presentations, work-up, and treatment of a 38-year-old Indian female patient with head and neck schwannoma in an atypical location. It was an incidental swelling noted during functional endoscopic sinus surgery. The tumor was found to be originating from the junction of the posterior and lateral pharyngeal wall near the lower edge of the torus tubarius on the left side. Complete surgical excision of the tumor was done in this case with no reported recurrence at 6 months’ follow-up. The final diagnosis was made on the basis of histopathology and immunohistochemistry findings. Conclusion Histopathology should serve as the foundation for a definitive diagnosis. Tumor removal can be carried out using minimally invasive surgery through the endoscopic approach, resulting in fewer complications and a lowered risk of morbidity.